2018
DOI: 10.1111/jon.12505
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High‐Frequency MRI Monitoring in the Detection of Brain Atrophy in Multiple Sclerosis

Abstract: High-frequency MRI monitoring may have a considerable effect on improving the precision of precisely identifying pathological BVL in individual patients. However, limitations in translation to clinical practice remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Finally, there was a significant aging interaction effect on increase in the PLVVC between HI and MS patients, which was not observed for the annualized PBVC. For all analyses, the results were similar for annualized (between first MRI and MRF) and annualized cumulative (including all serial MRI time points used in the analyses) rates of PLVVC and PBVC, in line with the findings from the previous study showing that serial MRI monitoring may only slightly improve the precision of brain atrophy measurement in individual subjects …”
Section: Discussionsupporting
confidence: 85%
“…Finally, there was a significant aging interaction effect on increase in the PLVVC between HI and MS patients, which was not observed for the annualized PBVC. For all analyses, the results were similar for annualized (between first MRI and MRF) and annualized cumulative (including all serial MRI time points used in the analyses) rates of PLVVC and PBVC, in line with the findings from the previous study showing that serial MRI monitoring may only slightly improve the precision of brain atrophy measurement in individual subjects …”
Section: Discussionsupporting
confidence: 85%
“…Many research groups are trying to address these issues by: (a) collecting MRI brain volumetric data from normal participants and MS patients using standardized protocols; (b) continuing to develop/improve methods to reduce measurement error; and (c) developing predictive models based on cross-sectional WBV measures. 47,48 The use of high frequency MRI monitoring, over both 12- and 24-month periods and using a segmentation-based analysis method (ScanView, an in-house developed software from Charles University, Prague, Czech Republic), was recently explored by Uher et al 49 It was concluded that high-frequency MRI performed over 12- and 24-month timeframes, may have a considerable effect on improving the precision of pathological BVL identification in individual patients. 49 However, the frequency of MRI acquisition required to gain optimal results (2-monthly MRI scans) would be impractical in a real-world clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The use of high frequency MRI monitoring, over both 12- and 24-month periods and using a segmentation-based analysis method (ScanView, an in-house developed software from Charles University, Prague, Czech Republic), was recently explored by Uher et al 49 It was concluded that high-frequency MRI performed over 12- and 24-month timeframes, may have a considerable effect on improving the precision of pathological BVL identification in individual patients. 49 However, the frequency of MRI acquisition required to gain optimal results (2-monthly MRI scans) would be impractical in a real-world clinical setting. The statistical association, consistency and agreement between the techniques used to measure absolute WBV in this study were excellent but were less impressive when normalized WBV measurements were compared.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unfortunately, a relatively high variability of brain atrophy measures renders challenging its application in individual MS patients. [2][3][4][5][6][7][8] Although MS is typically associated with accelerated brain volume loss, [3][4][5] there are cases where brain volume increase (BVI) appears to occur, particularly over short-time periods. 9 As consequence, apparent BVI may complicate the interpretation of brain volume change measurements in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of brain atrophy in individual multiple sclerosis (MS) patients could facilitate the identification of those with or without risk of disease progression 1 . Unfortunately, a relatively high variability of brain atrophy measures renders challenging its application in individual MS patients 2–8 . Although MS is typically associated with accelerated brain volume loss, 3–5 there are cases where brain volume increase (BVI) appears to occur, particularly over short‐time periods 9 .…”
Section: Introductionmentioning
confidence: 99%